Premiere Pro Guru: 3D Titling for Video Editors. - Stern, Eran (linkedin.com, 2016)
Work through four hands-on projects and create 3D titles using Premiere Pro. Create objects and type, animate text, apply transitions and camera effects, and solve for camera motion.